“Costos por procesos en la producción de banano en la Finca “La Soledad”, en el recinto Tres Coronas, parroquia El Carmen, cantón La Mana, provincia de Cotopaxi, año 2021” - Pastuña Sigcha, Tania Marcela (2021)
The research project is based on the process costs in the plantain production in La Soledad farm, which helped to identify the total cost of each production process through an analysis; which used bibliographic citations referring to the subject, that was of great help to have more knowledge of the subject and to be able to analyze; research methods, techniques and instruments were also used, which help to provide real and truthful information about the different operations carried out in plantain production; descriptive research, such as that in the field, helped to obtain information from the source, which benefited a great part to know how the farm is managed. The population of the company is also of vital importance, because it helped to carry out a survey of the workers and an interview with the general manager, contributing relevant information to the project under study. A process flow chart was determined where the four stages of the process were known, with the respective production cost: preparation of the land with $ 2,850.53 dollars; the maintenance of the plant $ 1268.31 dollars; cluster care $ 2,658.2 and harvest $ 3,620.00 adding a total production cost of $ 10,397.04.